Focused Review: Insight and Updates on COVID-19 from Progress in Microbes and Molecular Biology - Angel Yun-Kuan Thye; Jodi Woan-Fei Law (Progress in Microbes and Molecular Biology)
COVID-19 Bulletins from various countries have been published as the pandemic hit. This focused review provides an overview of the published COVID-19 cases, including the first case detected in respective countries, preventive measures implemented, and vaccinations available for some countries, depending on the time it was written. The countries that will be covered in this review are the United Kingdom, Spain, Malaysia, Singapore, Thailand, India, Australia, South Africa, and Brunei. This review also discusses the variants of concern (VOCs) that emerged since the start of the pandemic, which include variants: Alpha (B.1.1.7), Beta (B.1.351), Delta (B.1.617.2), Gamma (P.1), and Omicron (B.1.1.529). COVID-19-associated gastrointestinal manifestations and mental health implications and the application of probiotics as a potential adjunct therapy to psychotropic medications will be addressed in this review. Additional information on COVID-19 will also be reviewed, such as risk factors affecting COVID-19 case fatality rate, positive impacts of public health measures, the cost-effectiveness of public health strategies on COVID-19 control, and the COVID-19 pandemic and diet.